Panduan pendamping penilaian dasar kesejahteraan manusia - Colfer, C.J.P.; Brocklesby, M.A.; Diaw, C.; Etuge, P.; Günter, M.; Harwell, E.; McDougall, C.; Porro, N.M.; Porro, R.; Prabhu, Ravi; Salim, A.; Sardjono, M.A.; et al. (Center for International Forestry Research, 2000)
The Grab Bag' is designed to complement 'the BAG' and for use by social scientists who may find 'the BAG' overly prescriptive. The eight methods presented are either more difficult for non-social scientists to use or, in a couple of cases, can substitute for one or more method presented in 'the BAG'. 'The Scoring and Analysis Guide' provides the user with help in making an actual assessment of the social C&I, based on the results of these methods.